Behavioristic Learning Theory to Increase Motivation to Learn Mathematics Grade 2 Elementary School Students - Wardhana, Eka; Suarni, Ni Ketut; Margunayasa, I Gede (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Mathematics is one of the subjects that is considered the most difficult compared to other subjects which causes a decrease in student motivation in learning mathematics. This problem is reflected in low active participation, inability to maintain concentration, and decreased interest in mathematics subjects. This study aims to investigate the impact of the application of behavioristic learning theory in increasing learning motivation and understanding of mathematical concepts in grade 2 elementary school students. A total of 36 students were involved in the study, with two groups namely the experimental group and the control group. Data were collected through learning motivation questionnaires, classroom observations, and cognitive tests. Analysis of the data using the t-test showed significant differences between the two groups, with the experimental group experiencing greater increased motivation and understanding of mathematics. These results provide strong support for the effectiveness of behavioristic learning theory at the primary education level, with practical implications for the development of learning motivation-oriented learning strategies and academic outcomes. Matematika merupakan salah satu mata pelajaran yang dianggap paling sulit dibandingkan dengan mata pelajaran lain yang menyebabkan menurunnya motivasi siswa dalam belajar matematika. Permasalahan ini tercermin dari rendahnya partisipasi aktif, ketidakmampuan mempertahankan konsentrasi, dan menurunnya minat terhadap mata pelajaran matematika. Penelitian ini bertujuan untuk menginvestigasi dampak penerapan teori belajar behavioristik dalam meningkatkan motivasi belajar dan pemahaman konsep matematika pada siswa kelas 2 SD. Sebanyak 36 siswa terlibat dalam penelitian ini, dengan dua kelompok yaitu kelompok eksperimen dan kelompok kontrol. Data dikumpulkan melalui kuesioner motivasi belajar, observasi kelas, dan tes kognitif. Analisis data menggunakan uji t-test menunjukkan perbedaan signifikan antara kedua kelompok, dengan kelompok eksperimen mengalami peningkatan motivasi dan pemahaman matematika yang lebih besar. Hasil ini memberikan dukungan kuat terhadap efektivitas teori belajar behavioristik di tingkat pendidikan dasar, dengan implikasi praktis untuk pengembangan strategi pembelajaran yang berorientasi pada motivasi belajar dan hasil akademis.